Concise enantioselective synthesis of (+)-febrifugine - Emmanuvel, Lourdusamy; Kamble, Dayanand A.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-febrifugine, a potent antimalarial alkaloid, has been described based on the regioselective asymmetric dihydroxylation of a 1,4-dienic ester as the key step. The strategy also involves chemoselective [3,3]-sigmatropic rearrangement of 1,5-hexadiene-3-ol and intramolecular lactamization of azidolactone for the construction of piperidine core. (C) 2008 Elsevier Ltd. All rights reserved.